LAW ENFORCEMENT OF LAND GRACE - Robert Lengkong Weku; Andika Adhyaksa (Faculty of Law, Khairun University, 2023)
This study aims to analyze legal protection for acts of land grabbing and to analyze the prevention and handling of acts of land grabbing. The type of research used is normative legal research, relying on and using library data, namely secondary data in the field of law. The technique of obtaining legal materials is by means of library research by collecting legal materials by reading, quoting, recording and understanding various legal literature and laws. The results of the study show that 1) The legal provisions themselves have accommodated land grabbing in both criminal and civil aspects. 2) Enabling legal sanctions in forcing someone's obedience to the law as above contains aspects of prevention and enforcement aspects.